Fictionally fabulous the characters who created the looks we love - Higgins, Anne Keenan (Philadelphia Running Press, 2017)
"Fictionally Fabulous is a full-colour illustrated guide to dozens of beloved characters from film and TV who changed the face of fashion. From the flapper era embodied by Louise Brooks to polka dot-studded housewife Lucy Ricardo, Holly Golightly's immortal little black dress, working-girl chic Mary Richards, tartan-skirted Cher Horowitz in Clueless, to the Scandalous Olivia Pope, and all our favourite style stars in between. Each fashion hero is showcased in a whimsical style by author and illustrator Anne Keenan Higgins who offers views of their aha moments, inspiration boards, and profiles describing each character's signature style and trend-setting influence." -- Provided by publisher.
Keywords: Fashion -- History -- 20th century; Fashion -- History -- 21st century; Fashion in motion pictures